Zielzorg in het publieke domein: Over de legitimering van geestelijke verzorging - Gärtner, Stefan 1965-; Groot, C. N. de 1966-; Körver, Sjaak 1955- (2012)
Spiritual care in Dutch health care institutions is experiencing interesting times. The previous decade has witnessed a development in which denomination has taken second place to professionalism. This development means that the health care institution and the intended treatment and care have become a more important benchmark for spiritual care workers than their own denominational bonds, without these latter becoming inconsequential. If spiritual care wants to hold its own in health care institutions, referring to this denominational background and the right to practice one’s religion would seem to be insufficient. One’s own professional contribution to the institution’s objective is increasingly becoming an issue. Spiritual care’s identity, legitimacy and positioning are thus at risk, and with it the justification of spiritual care in the public domain. This latter applies from the perspective of the bodies conferring the mission as well as from that of the health care institutions. In the light of these developments, the authors discuss an interim report entitled Herkenbaar and betrouwbaar pastoraat [Recognisable and Reliable Pastoral Work] which is intended to result in the Dutch Bishops’ Conference’s Vademecum for chaplaincy. The interim report serves as a case-study for analysing the way in which bodies conferring missions (here the Roman Catholic bishops in the Netherlands) respond to current developments. Several developments have become a source of distress for the bishops; some are in the areas of church mission, liturgy and special moral questions. The interim report pointedly sets forth prevailing church regulations on these subjects. This article analyses the fact that the interim report does not seek dialogue but issues orders (to the directors of health care institutions no less than to catholic spiritual workers), that it starts from a uniformly Catholic target group and that spiritual care is primarily understood as proclamation and catechesis. This means that the report chooses for a specific (internal and external) legitimation. However, there remains the question whether this is an adequate answer to the present pluralism in the Dutch religious context and to the way professionals cooperate in a modern health care institution. This article seeks to provide an impetus for another type of legitimation for spiritual care in which professionalism and denominational interests remain in balance. Spiritual care workers and bishops will both find this new type challenging.